Degradability of Poly(lactic acid)-containing Nanoparticles: Enzymatic access through a crosslinked shell barrier - Samarajeewa, Sandani (2011)
Comparative studies of bulk samples of hydrolytically-degradable poly(lactic acid) (PLA) vs. core-shell block copolymer micelles having PLA cores revealed remarkable acceleration in the proteinase K enzymatic hydrolysis of the nanoparticulate forms, and demonstrated that even with amidation-based shell crosslinking, the core domain remained accessible. Kinetic analyses by (1)H NMR spectroscopy showed less than 20% lactic acid released from enzymatically- catalyzed hydrolysis of poly(L-lactic acid) in bulk, whereas ca. 70 % of the core degraded within 48 h for block copolymer micelles of poly(N-(acryloyloxy)succinimide-copolymer-N-acryloylmorpholine)-block-poly(L-lactic acid) (P(NAS-co-NAM)-b-PLLA), with only a slight reduction to ca. 50 % for the shell crosslinked derivatives. Rigorous characterization measurements by NMR spectroscopy, fluorescence spectroscopy, dynamic light scattering, atomic force microscopy, and transmission electron microscopy were employed to confirm core excavation. These studies provide important fundamental understanding of the effects of nanoscopic dimensions on protein-polymer interactions and polymer degradability, which will guide development of these degradable nanoconstructs to reach their potential for controlled release of therapeutics and biological clearance.